Environmental Awareness of Surf Tourists: A Case Study in the Algarve - Frank, Fabia; Pintassilgo, Pedro; Pinto, Patrícia (Journal of Tourism, Sustainability and Well-being, 2015)
Even though surf tourism in Portugal is an economic activity with a steady growth rate, there are not many assessment studies available. Using a survey undertaken in surf camps located in the Vila do Bispo County, this study aims to analyse the environmental awareness of surf tourists in the Algarve. Through the New Environmental Paradigm (NEP) scale it is shown that the environmental attitudes of respondents are strongly pro-ecological but also reveal some anthropocentric aspects. Tourists were asked about their willingness to pay for an accommodation tax earmarked for environmental protection in the Algarve. The results show that the large majority (86%) would be willing to pay, which indicates a high environmental awareness. It is also found that the willingness to pay is related to the nationality, with respondents from Germany, Austria and Switzerland showing a higher willingness to pay.